2018
DOI: 10.22161/ijaers.5.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Juice as a Natural Catalyse for Synthesis of Shiff’s base: A Green Chemistry Approach

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…It is also close to the results (19),in Iraq, Wasit province, which recorded the highest incidence in the category (7-9) years by 46.01%. The infection rate was high in children due to the scratching of the anus due to itching caused by parasite infection, eggs are picked under their nails and then deposited on toys or writing and eating, bad habits when the child with his fingers in his mouth, as well as overcrowded schools, nurseries, playgrounds this is consistent with (28). Who conducted several studies and their results showed that the low risk of gastrointestinal disease among children who wash their hands and the level of parental education are important factors and affect parasitic infection.…”
Section: Discussionsupporting
confidence: 62%
“…It is also close to the results (19),in Iraq, Wasit province, which recorded the highest incidence in the category (7-9) years by 46.01%. The infection rate was high in children due to the scratching of the anus due to itching caused by parasite infection, eggs are picked under their nails and then deposited on toys or writing and eating, bad habits when the child with his fingers in his mouth, as well as overcrowded schools, nurseries, playgrounds this is consistent with (28). Who conducted several studies and their results showed that the low risk of gastrointestinal disease among children who wash their hands and the level of parental education are important factors and affect parasitic infection.…”
Section: Discussionsupporting
confidence: 62%
“…In Type 2 diabetes, tissues don't respond to insulin. Similar to the type 1 increasing of glucotoxicity, lipotoxicity, and apoptosis lead to the progressive loss of beta cells in type 2 diabetes (20) .…”
Section: Discussionmentioning
confidence: 86%
“…The authors observed that the quantity of the biocatalysts affects the product yield whereby low amounts of the catalyst increased the product yield and vice-versa. Alikhani et al [41] also reported the synthesis of new Schiff bases 18 starting from aldehydes/ketones and 4,6diamino 2-thiol pyrimidine using lemon juice as a natural catalyst (Scheme 17). The synthesized compounds exhibited in vitro antibacterial activity against Escherichia Coli gramnegative strain of microbes.…”
Section: Synthesis Of Schiff Basesmentioning
confidence: 99%